Concern about the possibility of becoming a victim of extortion: validation of a brief scale for Peruvian citizens - Mamani-Benito, Oscar; Carranza Esteban, Renzo Felipe; Cruz Ordinola, María Celinda; Huayta-Meza, Mariné; Cruz-Campos, Cristhian; Pacheco-Vizcarra, Milagros Yesenia; Morales-Garcia, Wilter C. (Frontiers in Psychiatry, 2025)
IntroductionThe phenomenon of extortion is generating serious repercussions on the mental health of the economically active population. In the absence of measurement instruments to quantify the magnitude of this problem, it becomes urgent to design a documentary measurement tool.ObjectiveTo design and validate a scale measuring concern about the possibility of becoming a victim of extortion.MethodThe study is classified as instrumental. Using purposive non-probability sampling, participation was obtained from 2.049 citizens of both sexes across the three regions of Peru. The instrument was designed in 10 stages, following expert recommendations on the subject. The first version consisted of 11 items with five-point Likert-type response options. Analyses were conducted to demonstrate content validity, construct validity, convergent validity, measurement invariance, and reliability.ResultsAll items proved to be clear, relevant, and representative (V > 0.70). Exploratory factor analysis suggested an underlying structure composed of eight items (KMO = 0.91, Bartlett’s test = p ≤ 0.001), with factor loadings above the 0.40 cutoff (0.75 to 0.83). Subsequently, confirmatory factor analysis corroborated this unidimensional structure (SRMR = 0.037, RMSEA = 0.074, CFI = 0.996, TLI = 0.994). In addition, the BECS was shown to be invariant across sex and exhibited significant correlations with other comparable scales, thus providing evidence of convergent validity. Finally, the instrument demonstrated excellent reliability (>0.90).ConclusionThe BECS shows psychometric evidence supporting its validity and reliability. Therefore, it becomes the first measure available to assess concern about the possibility of becoming a victim of extortion.